(3QhM GdQhM ajeG MOK HYO GdeGFI GdJGSYI ef GdaJf hGdaJhMs - (3YjSi Hf dWa Gddg Hf GdeWgQ Hf jMji TQa GdOjf , GHf GdeWgQ,J (B1048 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi Gdedc hGdedchJhHYO Efg CdRefi ef dGjSYfi NdGag deG LQi ai ebGeg PcQ NQhL GdTQGcSI Edi Gdjef hXghQ Jdc GdCMOGK hGdaJf hSejJg QhM GdQhM s
(3BNQgG (B:s
(3hcGfJ haGI ehdGfG CMeO Hf jMji Hf GdeQJVi ai UMhI jhe GdSHJ KGfi YTQ TgQ UaQ SfI CQHYjf hKeGfeGFI HeMQhS GdWajQ Je GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3ebGHdI Ydi fSNJjf s
(3cJHJ HYV cdeGJgG HGdMeQI s
(3hgfGc cdeGJ cJHJ HGdUaQI s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs